2021
DOI: 10.1016/j.yjmcc.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine maintains cardiac transverse-tubule structure and function

Abstract: Subclinical hypothyroidism and low T3 syndrome are commonly associated with an increased risk of cardiovascular disease (CVD) and mortality. We examined effects of T3 on T-tubule (TT) structures, Ca 2+ mobilization and contractility, and clustering of dyadic proteins.Thyroid hormone (TH) deficiency was induced in adult female rats by propyl-thiouracil (PTU; 0.025%) treatment for 8 weeks. Rats were then randomized to continued PTU or triiodo-L-thyronine (T3; 10 μg/kg/d) treatment for 2 weeks (PTU + T3). After i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Although TSH is considered to be the most sensitive marker for thyroid function [4], low circulating FT3 is the most frequently encountered thyroid functional test abnormality seen in CKD patients [11]. The HD patients enrolled in the present study were restricted to those with normal TSH, though it is becoming increasingly recognized that serum FT3 is more important than serum TSH for evaluating thyroid gland function because of its direct action in the target tissue [22]. A previous study also showed that the serum FT3/FT4 ratio clearly indicates a reduction in thyroid function in affected patients and the severity of low T3 syndrome [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although TSH is considered to be the most sensitive marker for thyroid function [4], low circulating FT3 is the most frequently encountered thyroid functional test abnormality seen in CKD patients [11]. The HD patients enrolled in the present study were restricted to those with normal TSH, though it is becoming increasingly recognized that serum FT3 is more important than serum TSH for evaluating thyroid gland function because of its direct action in the target tissue [22]. A previous study also showed that the serum FT3/FT4 ratio clearly indicates a reduction in thyroid function in affected patients and the severity of low T3 syndrome [23].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed an association between TH deficiency, disorganized T tubules, and reduced RYR2 cluster size/number. TH treatment increased the expression of junctophilin2 ( JPH2) as the critical regulator of cardiac dyad structure, and enhanced T-tubules network and RYR2 organization ( 81 ).…”
Section: Signaling Pathways Potentially Associated With Human Induced...mentioning
confidence: 99%
“…Low triiodothyronine (T3) syndrome, also known as euthyroid disease syndrome (ESS) or non-thyroid disease syndrome (NTIS), is characterized by decreased peripheral T3 concentration and normal thyroid stimulating hormone (TSH), on behalf of the thyroid hormone metabolism changes [ 8 ], common in severe patients, as well as some acute and chronic disease patients. Low T3 syndrome is generally associated with cardiovascular disease (CVD) and increased risk of death [ 8 ], which is often observed in acute myocardial infarction, is associated with myocardial injury and poor prognosis [ 9 11 ], and is also associated with high mortality in hospitalized patients with heart failure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low triiodothyronine (T3) syndrome, also known as euthyroid disease syndrome (ESS) or non-thyroid disease syndrome (NTIS), is characterized by decreased peripheral T3 concentration and normal thyroid stimulating hormone (TSH), on behalf of the thyroid hormone metabolism changes [ 8 ], common in severe patients, as well as some acute and chronic disease patients. Low T3 syndrome is generally associated with cardiovascular disease (CVD) and increased risk of death [ 8 ], which is often observed in acute myocardial infarction, is associated with myocardial injury and poor prognosis [ 9 11 ], and is also associated with high mortality in hospitalized patients with heart failure [ 12 ]. More and more evidence indicates that low T3 syndrome is a predictor of poor prognosis in patients with community acquired pneumonia [ 13 ], suppurative liver abscess [ 14 ], hemodialysis (HD) [ 15 ], autoimmune encephalitis (AE) [ 16 ], and brain tumor surgery [ 17 ] and is also associated with hemorrhagic transformation in patients with acute ischemic stroke [ 18 ].…”
Section: Introductionmentioning
confidence: 99%